Comparison of numerical ODE solvers based on Euler methods - İnç, Mustafa; Bildik, Necdet; Bulut, Hasan (Assoc Sci Res, 1998)
A class of nonlinear methods based on Euler's integration formula for the numerical solution of ordinary differential equations is presented. Numerical example involving stiff linear systems of first-order differential equations are given for test problem.
Keywords: Integration; Numerical analysis; Problem solving; Euler methods; Ordinary differential equations